Problematic alcohol use and sexting as risk factors for sexual assault among college women. Issue 7 (3rd October 2018) - Dir, Allyson L.; Riley, Elizabeth N.; Cyders, Melissa A.; Smith, Gregory T.
ABSTRACT: Sexual assault is a major public health concern and college women are four times more likely to experience sexual assault than any other group. We investigated whether sexting is a mechanism by which alcohol use increases risk for college women to be targeted for sexual assault. We hypothesized that sexting would mediate the relationship between problem drinking and sexual assault, such that drinking (T1 = beginning fall semester) would contribute to increased sexting (T2 = end fall semester), and in turn increase the risk of being targeted for sexual assault (T3 = end spring semester). Results : Among 332 undergraduate women ( M (SD)age = 19.15(1.69), 76.9% Caucasian), sexting (T2) predicted sexual assault (T3; b = 3.98, p = .05), controlling for baseline sexual assault ( b = 0.82, p < .01). Further, sexting (T2) mediated the relationship between problem drinking (T1) and sexual assault (T3) ( b = 0.04, CI[.004, .12]). Conclusion : Findings suggest that sexting is one mechanism through which drinking increases the risk of college women being targeted for sexual assault.